Analysis of capital turnover and price for finished products in the AIC integrated associations - G. A. Arshinov; S. V. Laptev; V. G. Arshinov (Новые технологии, 2018)
Conditions for the formation of effective associations of enterprises in a dairy sub-complex of the agro-industrial complex have been investigated on the basis of a mathematical model of an agricultural consumer cooperative. Price policy formation of the enterprise processing raw materials have been analyzed taking into account the turnover of invested capital.